2016
DOI: 10.1097/igc.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

Oral Progestin Treatment for Early-Stage Endometrial Cancer: A Systematic Review and Meta-analysis

Abstract: Based on the present systematic review and meta-analysis, oral progestin treatment is feasible and safe for patients of reproductive age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 48 publications
2
43
1
Order By: Relevance
“…Conversely, two recurrences were recorded in patients who had successfully finished their pregnancies. The median number of D&C undergone by those who gave birth was three (range, [3][4][5][6][7][8][9]. No cases of placenta accreta were recorded.…”
Section: Pregnancies After Mpa Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, two recurrences were recorded in patients who had successfully finished their pregnancies. The median number of D&C undergone by those who gave birth was three (range, [3][4][5][6][7][8][9]. No cases of placenta accreta were recorded.…”
Section: Pregnancies After Mpa Treatmentmentioning
confidence: 99%
“…For this reason, the use of high‐dose oral medroxyprogesterone acetate (MPA) as a fertility‐sparing treatment for EC and AEH has attracted interest. Although oral progestin treatment including MPA can achieve a complete response in many patients, a high rate of recurrence has been reported . Hysterectomy is often recommended to patients with recurrence, but almost all of these patients are reluctant to undergo the procedure following only a single relapse, with many requesting the re‐administration of MPA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature shows that oral progestin therapy can achieve CR rates ranging between 67 and 80% (4-8). Our recent metaanalysis found that among 445 grade 1 stage IA EC patients who administered oral progestin, the remission rate was 82.4% (10). The pregnancy rate was 28.8%, and the recurrence rate was 25% (10).…”
Section: Discussionmentioning
confidence: 98%
“…Our recent metaanalysis found that among 445 grade 1 stage IA EC patients who administered oral progestin, the remission rate was 82.4% (10). The pregnancy rate was 28.8%, and the recurrence rate was 25% (10). The differentiation degree of EC is the most important indicator to predict stage and response to progestin treatment (11).…”
Section: Discussionmentioning
confidence: 99%